Dysregulation of REST‐regulated coding and non‐coding RNAs in a cellular model of Huntington's disease. (7th January 2013) - Soldati, Chiara; Bithell, Angela; Johnston, Caroline; Wong, Kee‐Yew; Stanton, Lawrence W.; Buckley, Noel J.
Abstract Huntingtin (Htt) protein interacts with many transcriptional regulators, with widespread disruption to the transcriptome in Huntington's disease (HD) brought about by altered interactions with the mutant Htt (muHtt) protein. Repressor Element‐1 Silencing Transcription Factor (REST) is a repressor whose association with Htt in the cytoplasm is disrupted in HD, leading to increased nuclear REST and concomitant repression of several neuronal‐specific genes, including brain‐derived neurotrophic factor (Bdnf). Here, we explored a wide set of HD dysregulated genes to identify direct REST targets whose expression is altered in a cellular model of HD but that can be rescued by knock‐down of REST activity. We found many direct REST target genes encoding proteins important for nervous system development, including a cohort involved in synaptic transmission, at least two of which can be rescued at the protein level by REST knock‐down. We also identified several microRNAs (miRNAs) whose aberrant repression is directly mediated by REST, including miR‐137, which has not previously been shown to be a direct REST target in mouse. These data provide evidence of the contribution of inappropriate REST‐mediated transcriptional repression to the widespread changes in coding and non‐coding gene expression in a cellular model of HD that may affect normal neuronal function and survival.